2017
DOI: 10.21746/ijbio.2017.9.2
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Nigella Sativa oil extract against neurotoxicity induced by Valproic acid

Abstract: Nigella sativa (NS), commonly known as black cumin, has been used for medicinal purposes. Traditionally the seeds and its oil are used in several diseases. The greatest part of the remedial properties of this plant is due to the presence of thymoquinone (TQ) which is a major active chemical component of the essential oil. The current study performed to evaluate the effect of Nigella sativa oil (NSO) extract on the neurotoxic and hepatotoxic potentials from valproic acid (VPA) administration. Also we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…The liver function enzymes [Alanine Amino Transferase (ALT), Alkaline Phosphatase (ALP), Aspartate Amino Transferase (AST), Gamma Glutamyl Transferase (GGT)] serum activities are used as biomarkers of liver damage as leakage of these enzymes into blood stream is associated with hepatocyte injury [56]. A very sensitive indicator of insult to hepatocyte is the release of liver enzymes such as AST and ALT after VPA intoxication [52], the elevated activities as seen in this study indicated hepatocellular damage which concur with the study by Morsy et al [7]. AST is distributed in the body tissues; including muscle, heart and liver while ALP in the liver, kidney and bone.…”
Section: Fig 3 Photomicrograph Of Heamatoxylin and Eosin Stained Lusupporting
confidence: 87%
See 1 more Smart Citation
“…The liver function enzymes [Alanine Amino Transferase (ALT), Alkaline Phosphatase (ALP), Aspartate Amino Transferase (AST), Gamma Glutamyl Transferase (GGT)] serum activities are used as biomarkers of liver damage as leakage of these enzymes into blood stream is associated with hepatocyte injury [56]. A very sensitive indicator of insult to hepatocyte is the release of liver enzymes such as AST and ALT after VPA intoxication [52], the elevated activities as seen in this study indicated hepatocellular damage which concur with the study by Morsy et al [7]. AST is distributed in the body tissues; including muscle, heart and liver while ALP in the liver, kidney and bone.…”
Section: Fig 3 Photomicrograph Of Heamatoxylin and Eosin Stained Lusupporting
confidence: 87%
“…One of such drugs with widely reported toxicity is HDAC inhibitor, sodium valproate or valproic acid. VPAinduced global toxicity relating to neurotoxicity [7], hepatotoxicity [8], hematotoxicity [9], nephrotoxicity [10], pancreatitis [11], bone marrow suppression [12], teratogenicity and developmental toxicity [13,14] and numerous idiopathic effects which in the offspring might lead to autistic spectrum disorder [15,16]. Sodium valproate is 2-propylpentanoic acid, first marketed about 45 years ago for the management of epilepsy [17], is generally prescribed mood stabilizer and anti-convulsant used to control generalized and partial seizures [18].…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐exposure to NSE at 10, 30, and 50 μg/ml of significantly preserved GSH content and ameliorated the LPO level of HUVECs in a concentration‐dependent way. It has been reported that N. sativa extracts (NSE) prevented against valproic acid‐induced alterations in antioxidant enzymes GSH and LPO (Morsy, Safwat, Hussein, & Samy, 2017). The preventive potential of N. sativa seeds on reduced GSH and increased LPO in erythrocytes of boiler chickens have also been reported (Tuluce, Ozkol, Sogut, & Celik, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium valproate is indicated worldwide for management generalized and partial seizures and numerous other neurological and psychiatric conditions [7][8][9]. Though it is a broad-spectrum antiepileptic drug it is usually well tolerated, but posit toxicities concerns [16][17][18][19][20][21][22][23][24][25]. As valproic acid is a branched chain carboxylic acid (2propylpentanoic acid or di-n-propyl acetic acid) and very similar to short-chain fatty acids, making VPA a substrate for the fatty acid oxidation pathways [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Variability in VPA tissues concentration have been observed in different organs (brain and kidney) and the plasma suggestive of variable tissue transport mechanism [5]. The low permeability of SVPA to the brain necessitates a relatively high daily dosage which posit adverse effects such as bone marrow suppression [16], lethargy [5], hepatotoxicity [17], nephrotoxicity [18], teratogenicity and developmental toxicity [19,20], neurotoxicity [21] , hematotoxicity [22], pancreatitis [23], and numerous idiopathic effects which in the offspring might lead to autistic spectrum disorder [24,25]. The drug carries a black box warning for life-threatening adverse drug reactions (ADR) including hepatotoxicity, teratogenicity and pancreatitis [26].…”
Section: Introductionmentioning
confidence: 99%